Association of Leptin Gene Polymorphisms with Rheumatoid Arthritis in a Chinese Population. (6th October 2020) - Tao, Sha-Sha; Dan, Yi-Lin; Wu, Guo-Cui; Zhang, Qin; Zhang, Tian-Ping; Fan, Yin-Guang; Pan, Hai-Feng
Abstract : Background . Recently, increasing studies have revealed that leptin is involved in the development of rheumatoid arthritis (RA). This study is aimed at exploring the association of leptin gene single nucleotide polymorphisms (SNPs) with susceptibility to RA in a Chinese population. Methods . We recruited 600 RA patients and 600 healthy controls from a Chinese population and analyzed their three leptin SNPs (rs10244329, rs2071045, and rs2167270) using the improved Multiplex Ligase Detection Reaction (iMLDR) assays. The associations of these SNPs with clinical manifestations of RA were also analyzed. Enzyme-linked immunosorbent assay (ELISA) was performed for plasma leptin determination. Results . No significant difference in either allele or genotype frequencies of these three SNPs between RA patients and healthy controls was observed (all P > 0.05 ). Association between the genotype effects of dominant, recessive models was also not found (all P > 0.05 ). No significant difference in plasma leptin levels was detected between RA patients and controls (P > 0.05 ). Conclusion . Leptin gene (rs10244329, rs2071045, and rs2167270) polymorphisms are not associated with RA genetic susceptibility and its clinical features in the Chinese population.